Innovative Design of Waterbase Aerodrome: Integration of Technology and Sustainability - Ikhwanul Qiram (Politeknik Transportasi Sungai, Danau dan Penyeberangan Palembang, 2023)
This literature review explores the various aspects of waterbase aerodromes, including design elements, technology integration, sustainability considerations, and safety measures. The study reveals that waterbase aerodromes require careful attention to technical aspects to ensure their successful development. The integration of advanced materials, navigation systems, and communication technologies enhances their efficiency and performance. Sustainability practices, such as the use of renewable energy sources and ecological conservation, play a crucial role in minimizing environmental impact. Safety considerations, including emergency response systems and comprehensive training, ensure the well-being of passengers and infrastructure. This review provides valuable insights for designing and operating efficient, sustainable, and safe waterbase aerodromes